Application of GNSS Methods for Monitoring Offshore Platform Deformation - Myint, K.C. (EDP Sciences, 2018)
Global Navigation Satellite System (GNSS) has become a powerful tool for high-precision deformation monitoring application. Monitoring of deformation and subsidence of offshore platform due to factors such as shallow gas phenomena. GNSS is the technical interoperability and compatibility between various satellite navigation systems such as modernized GPS, Galileo, reconstructed GLONASS to be used by civilian users. It has been known that excessive deformation affects platform structurally, causing loss of production and affects the efficiency of the machinery on board the platform. GNSS have been proven to be one of the most precise positioning methods where by users can get accuracy to the nearest centimeter of a given position from carrier phase measurement processing of GPS signals. This research is aimed at using GNSS technique, which is one of the most standard methods to monitor the deformation of offshore platforms. Therefore, station modeling, which accounts for the spatial correlated errors, and hence speeds up the ambiguity resolution process is employed. It was found that GNSS combines the high accuracy of the results monitoring the offshore platforms deformation with the possibility of survey. Â© The Authors, published by EDP Sciences, 2018.